Despertar da percepção na educação infantil: caminhos para uma aprendizagem totalizante - Cardoso, Débora da Silva (2013)
This research discussed the awakening of perception of the child and the teacher in the first stage of early childhood education with regard to themselves, to others and to the environment as a source to rescue the sensitivity in educational activities, seeing as art a way for aesthesia, experienced through proposals that valued the body as a source of meaning and knowledge and outlining ways that implemented the learning totalizing process of teaching and learning. The route outlined was the result of dissatisfaction with the proposed learning not explored the senses of the body, keeping it anesthetized, plastered with models ready, absent of understanding and reflection, and distant from the real needs of students. The actions developed in the study were inspired by the Phenomenology of Perception by Maurice Merleau-Ponty that based theoretically develop the project "Children doing art" wich was the focus of this analysis. We opted for a qualitative approach, which constitutes a more appropriate guideline to understand the context in which the research was conducted: group of children in the first stage of early kindergarten education and the learning process in this group. It was collected descriptive data through joint use of observation, interviews, photographic documentation , interview and instruments for which individuals were observed and analyzed by means of a case study - this search a student and their teacher in an educational institution. The results were significant because there was a new look at the theme of perception contributed to sharpen the perceive yourself, others and the environment, providing greater proximity of teachers and their students and the presence of greater sensitivity in educational activities, because the understand and be aware of the needs of the student become essential ingredients in this process. The exploration of the senses of the body in the proposals currently teaching is valued and, consequently, there was an increase in expressive communication, oral communication and interaction among children. A keen perception, sensitivity in educational activities, the appropriate approach to the teacher and his pupil, the amount owing to the senses of the body opened up avenues for the acquisition of Learning totalizing. With these results aims - to contribute to the educational projects of kindergarten education that have poor corporeality assumed a "way light and loose" allowing children to the full development of their identities through play, express themselves , interact, if move through the school, such as projects present themselves plastered by mechanical activities, without any understanding and reflection, almost excluded moments of artistic expression in childhood coherently, which sees the child as an individual and your body as a source of interaction and knowledge. These results showed that teachers who invest in education with sensitivity and sharpened perception, achieve success in the learning of their students.